On the verification of non-autonomous Petri net models using autonomous petri net tools - Barros, João Paulo (2013)
This paper shows how to transform the input part of a class of non-autonomous Petri net models into behaviorally equivalent autonomous models. To that end, it proposes a set of transformations and compositions to replace non-autonomous annotations by structurally equivalent net modules. The resulting model can be analyzed by existing tools for autonomous Place/Transition nets supporting a maximal step semantics and, preferably, priorities in transitions. This possibility was tested using a freely available analysis tool for Place/Transition nets.